2019
DOI: 10.1039/c9ra06774d
|View full text |Cite
|
Sign up to set email alerts
|

Protein-activated transformation of silver nanoparticles into blue and red-emitting nanoclusters

Abstract: Protein capping can trigger nanoparticle to nanocluster transformation at elevated pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…Over the years, atomically precise noble metal nanoclusters (MNCs) have received immense interest due to widespread opportunities in sensing, multimodal imaging, , targeted drug delivery, therapeutic applications, , biolabeling, , and so on. , These MNCs feature unique molecule-like fluorescence (FL) properties due to the presence of discrete energy levels, unlike their larger plasmonic nanoparticle counterparts . Contrary to most extensively studied gold nanoclusters (AuNCs), silver nanoclusters (AgNCs) remain less explored due to their propensity to aggregate in an aqueous phase because of their higher surface energy, making the synthesis of AgNCs a bit challenging. , Particularly, proteins as stabilizers have come out as a boon to researchers presenting a bio-friendly avenue to produce water-soluble and stable AgNCs. However, toxic reducing agents such as NaBH 4 are often used to synthesize most red-emitting protein-stabilized AgNCs, which may limit their application in a biological system. , Zhou et al synthesized red-emitting AgNCs using NaBH 4 as a reducing agent and lysozyme (LYS) as a stabilizer . However, the quantum yield (QY) was only 1.3%.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, atomically precise noble metal nanoclusters (MNCs) have received immense interest due to widespread opportunities in sensing, multimodal imaging, , targeted drug delivery, therapeutic applications, , biolabeling, , and so on. , These MNCs feature unique molecule-like fluorescence (FL) properties due to the presence of discrete energy levels, unlike their larger plasmonic nanoparticle counterparts . Contrary to most extensively studied gold nanoclusters (AuNCs), silver nanoclusters (AgNCs) remain less explored due to their propensity to aggregate in an aqueous phase because of their higher surface energy, making the synthesis of AgNCs a bit challenging. , Particularly, proteins as stabilizers have come out as a boon to researchers presenting a bio-friendly avenue to produce water-soluble and stable AgNCs. However, toxic reducing agents such as NaBH 4 are often used to synthesize most red-emitting protein-stabilized AgNCs, which may limit their application in a biological system. , Zhou et al synthesized red-emitting AgNCs using NaBH 4 as a reducing agent and lysozyme (LYS) as a stabilizer . However, the quantum yield (QY) was only 1.3%.…”
Section: Introductionmentioning
confidence: 99%
“…Jin and co-workers synthesized Ag 7 NCs with high yield by the reduction of AgNO 3 using meso-2,3-dimercaptosuccinic acid (DMSA) ligands . Blue-light-emitting AgNCs was synthesized by bovine serum albumin (BSA) as capping molecules with high quantum yield . Rotello and co-workers reported polyethylenimine-functionalized cationic AgNCs as potent antimicrobials against multidrug-resistant bacteria .…”
Section: Introductionmentioning
confidence: 99%
“…31 Blue-light-emitting AgNCs was synthesized by bovine serum albumin (BSA) as capping molecules with high quantum yield. 32 Rotello and co-workers reported polyethylenimine-functionalized cationic AgNCs as potent antimicrobials against multidrug-resistant bacteria. 33 Red-emitting AgNCs were synthesized using poly(methacrylic acid) as a template under UV irradiation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previously it has been reported that the reduced-cysteine residues have strong interactions with silver nanoparticles (AgNPs), which play roles in maintaining its native conformations [12]. Biologically synthesized (B-AgNPs) interact with proteins and form a dynamic B-AgNPs-protein corona which probably influences unfolding and refolding pathway resulting in protein aggregation inhibition and chaperone-like activity [13].…”
Section: Introductionmentioning
confidence: 99%